Karakteristik Fisiologis Lumut pada Beberapa Ketinggian di Kawasan Gunung Tangkuban Perahu - HIRMAS FUADY PUTRA; DHENOK SEKAR AMBARWATI; NURRIZKI MUBYRASIH; TERSI ALESTI (Jurnal Sumberdaya Hayati, 2015)
Environmental factors greatly influence the physiological state of moss. Some of the environmental factors that influence the physiological of moss are air temperature, humidity, and light intensity. These three environmental factors will vary at each altitude. This study aims to determine the physiological characteristics of mosses on some altitudes in the area of Mount Tangkuban Perahu (Ratu Crater – Domas Crater track). The method that are used is to measure air temperature, humidity, and light intensity at some altitudes. Subsequently, samples were taken at each altitude, to measured chlorophyll and proline content. Mosses that are used as samples; Campylopus sp., Plagiochila sp., Dicranella sp. The results indicate that the chlorophyll content significantly different at some altitude, with an increasing trend as the decrease altitude. The highest chlorophyll content in Campylopus sp. at altitude of 1,621 meters above sea level, while the lowest chlorophyll content in Plagiochila sp. at altitude of 1,721 meters above sea level. The content of proline did not differ significantly at some altitude, and tend to be more affected by air conditions that correlate with distance of moss habitat with the active crater of Domas, which allegedly can cause physiological stress in the moss.